2009
DOI: 10.1074/jbc.m809506200
|View full text |Cite
|
Sign up to set email alerts
|

Control of Alternative Splicing by Signal-dependent Degradation of Splicing-regulatory Proteins

Abstract: Alternative pre-mRNA splicing is a major gene expression regulatory mechanism in metazoan organisms. Proteins that bind pre-mRNA elements and control assembly of splicing complexes regulate utilization of pre-mRNA alternative splice sites. To understand how signaling pathways impact this mechanism, an RNA interference screen in Drosophila S2 cells was used to identify proteins that regulate TAF1 (TBP-associated factor 1) alternative splicing in response to activation of the ATR (ATM-RAD3-related) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Among these candidates, the Half-pint (Hfp) protein, also known as Puf68, was selected for further analysis as it has previously been implicated in the regulation of alternative splicing. 30,32 the protein binds relative to the affected splice site. [21][22][23][24] In the studies of Tra2, it was observed that Tra2 bound at intronic positions elicits splicing repression, but binding at exonic positions causes splicing activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these candidates, the Half-pint (Hfp) protein, also known as Puf68, was selected for further analysis as it has previously been implicated in the regulation of alternative splicing. 30,32 the protein binds relative to the affected splice site. [21][22][23][24] In the studies of Tra2, it was observed that Tra2 bound at intronic positions elicits splicing repression, but binding at exonic positions causes splicing activation.…”
Section: Resultsmentioning
confidence: 99%
“…32,40,41 These two factors were both among a small group of RNA binding proteins shown to be required to regulate splicing of mRNA encoding the Taf1-3 and Taf1-4 isoforms from the Drosophila Taf1 gene. The similar dependence of Taf1 on these two factors suggests that perhaps regulation occurs through a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Rox8 encodes a RNA-binding protein that controls important aspects of development, including alternative splicing and stress granule formation (39,40). In addition, we have previously performed an unbiased genetic screen for factors modulating JNK signaling (41), and identified Rox8 as a positive regulator of JNK signaling for Rox8 expression synergistically enhances Egr-induced JNK-dependent cell death (Fig.…”
Section: Jnk Is Required For Hippo Activation-induced Border Cell Migmentioning
confidence: 99%
“…SR proteins can also repress alternative splicing through multiple mechanisms, including acting through intronic splicing silencer elements (ISSs) adjacent to an alternative exon (Kanopka et al 1996;Buratti et al 2007). Modulation of SR proteins by small molecules has been shown in some studies, and they present interesting therapeutic targets for misregulated alternative splicing events (Soret et al 2005;Katzenberger et al 2009). …”
Section: Introductionmentioning
confidence: 99%